Climate change and air quality: The potential impact on health - Spickett, Jeffery; Brown, Helen; Rumchev, Krassi (Sage Publications, Inc., 2011)
The objectives of the study were to: consider the potential health impacts in Australia and the region arising from changes in air quality occurring as a result of climate change, identify vulnerable groups and potential adaptation measures and discuss the implications for policy. The authors provide an overview of international and national information on the potential health impacts of air pollutants that would most likely be affected by climate change and a discussion of the policy implications. Climate change is likely to have an impact on levels of ozone and possibly particulates, both of which are associated with increased mortality and a range of respiratory and cardiovascular health effects. One of the implications is therefore a possible increase in adverse health effects due to air pollutants. Regional health impact assessments of climate change should address the issue of air quality, consider current coping capacity, and determine the need for adaptation, particularly for vulnerable groups. Implications for policy include the need for improved modeling and forecasting of air pollutant levels, increased efforts to reduce emissions of air pollutants, continued monitoring of air pollutant levels, and monitoring of the incidence of health effects associated with air pollutants in all countries in the region.